A critical discourse analysis on self-efficacy values in modern Chinese children's stories - Muzaki, Ferril Irham (Diksi, 2022)
This review article will explain teaching materials for self-efficacy in modern Chinese children's stories. The materials focused on five grand topics. The topics are (1) find the moral values of thinking creatively, (2) find moral messages to design mapping the problems, (3) find normative values of work in order, (4) find moral values of taking initiative, (5) find moral values of thinking systematically. The method adopted by Fairclough's (2001) construction analysis on critical discourse analysis. Data taken from children's stories, these (1) Immortal Devil Transformation, (2) Warlock of the Magus World, (3) Wu Dong Kian Kun, (4) Dragon Prince Yuan, (5) Great Demon (7) A Record of a Mortal's Journey to Immortality, (8) Dragon Prince Yuan, (9) God of Cooking, (10) I Shall Seal the Heavens, (11) Heaven's Devourer, (12) Desolate Era, (13) the Human Emperor, (14) A Will Eternal, (15) Fields of Gold, and (16) Cultivation Online. Those stories were written in the periods 2005-2021. The results of this research indicate that self-efficacy in Chinese children's literature reflected on 6 results, those are (1) working based on problem solving, (2) working based on critical analysis, (3) working based on real facts, (4) working based on cognizance and (5) working based on integrity. The conclusion of this study is that self-efficacy in fantasy stories of Chinese children learning character education is based on exposure to universal values of self-efficacy. Keywords: self efficacy, ethics in schools, character education, children literature, chinese modern stories